2008
DOI: 10.1111/j.1460-9592.2008.02687.x
|View full text |Cite
|
Sign up to set email alerts
|

Does ketamine affect intraoperative electrophysiological monitoring in children undergoing selective posterior rhizotomy?

Abstract: Administration of low dose ketamine preceding the stimulation of dorsal roots during selective posterior rhizotomy might be associated with lower maximal thresholds and a more sustained train response following stimulation. Physicians should be aware of this finding in order to avoid misinterpreting intraoperative electrophysiological monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…As physicians gained practice through more IONM-guided SDR procedures, they became gradually aware of the importance of anesthesia during surgery when EMG responses are required to be interpreted in a standardized manner. Studies have shown that different anesthetics can affect intraoperative electrophysiological outcomes [16][17][18], including changes in threshold, latency to stimulus, and EMG response patterns. Because, to date, there is no proven anesthetic protocol used specifically for SDR, clinical practitioners have either just applied those protocols conducted in other neurosurgical procedures requiring IONM or simply developed their own [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Anesthesiamentioning
confidence: 99%
“…As physicians gained practice through more IONM-guided SDR procedures, they became gradually aware of the importance of anesthesia during surgery when EMG responses are required to be interpreted in a standardized manner. Studies have shown that different anesthetics can affect intraoperative electrophysiological outcomes [16][17][18], including changes in threshold, latency to stimulus, and EMG response patterns. Because, to date, there is no proven anesthetic protocol used specifically for SDR, clinical practitioners have either just applied those protocols conducted in other neurosurgical procedures requiring IONM or simply developed their own [2][3][4][5][6][7][8][9][10][11][12][13].…”
Section: Anesthesiamentioning
confidence: 99%